2014
DOI: 10.5935/0101-2800.20140026
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive capacity in individuals with chronic kidney disease: relation to demographic and clinical characteristics

Abstract: The average MMSE score declined with increasing age and increased with years of schooling and income per capita. No relationships were found to justify the harmful effects of dialysis process on cognition and memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 37 publications
3
13
0
9
Order By: Relevance
“…The results evidenced a moderate and statistically significant positive correlation (rho = 0.369, p = 0.045), suggesting that, the longer the time since the diagnosis of CKD, the higher the education level, not sustaining H3. In view of the low education and socioeconomic levels among the participants in this and other studies (Costa et al, 2012;Lopes et al, 2014;Melo et al, 2014;Silva et al, 2014), studies involving people with higher education levels and good socioeconomic conditions could try to better understand how the sociodemographic and health variables are related.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The results evidenced a moderate and statistically significant positive correlation (rho = 0.369, p = 0.045), suggesting that, the longer the time since the diagnosis of CKD, the higher the education level, not sustaining H3. In view of the low education and socioeconomic levels among the participants in this and other studies (Costa et al, 2012;Lopes et al, 2014;Melo et al, 2014;Silva et al, 2014), studies involving people with higher education levels and good socioeconomic conditions could try to better understand how the sociodemographic and health variables are related.…”
Section: Discussionmentioning
confidence: 85%
“…Other losses, such as the loss of functional capacity and financial losses (Guerra-Guerrero, Sanhueza-Alvarado, & CaceresEspina, 2012;Lopes et al, 2014;Silva et al, 2014), become even more prominent when family support is lacking (Terra et al, 2010).…”
Section: Viviane Gregoleti Universidade De Passo Fundo Passo Fundo-rmentioning
confidence: 99%
See 1 more Smart Citation
“…Segundo Censo de 2011 do Instituto Brasileiro de Geografia e Estatística, a taxa de fecundidade das mulheres brasileiras com menor nível de escolaridade foi de 3,07 filhos enquanto que mulheres com oito ou mais anos de estudos apresentaram taxa de 1,69 (NIEDERAUER, 2012). A relação entre a escolaridade e declínio cognitivo está bem estabelecida na literatura (BERTOLUCCI et al, 1994;SILVA et al, 2014). Assim, pode-se sugerir que pessoas com menor nível de escolaridade possuem maior número de filhos e isto pode resultar em maior chance de declínio cognitivo.…”
Section: Resultsunclassified
“…Among the clinical symptoms and signs of patients with CKD, anemia has been documented as a risk factor for cognitive decline, and a reversal of anemia in patients with CKD resulted in improvement in cognitive function [24,25]. Silva et al [26] found that the routine dialysis process had no harmful effect on cognition and memory.…”
Section: Introductionmentioning
confidence: 99%